The importance of improving food safety in Africa: Training by itself will rarely improve food safety - Grace, Delia (Technical Centre for Agricultural and Rural Cooperation, 2018)
Unsafe food causes widespread ill health and economic losses. A wide range of innovations are needed to improve safety standards and global public health.